پاکستان میں عدالتی نظام کی تشکیلِ نو: سید ابوالاعلیٰ مودودیؒ اور علامہ محمد اسدؒ کے افکار کا تقابلی و تجزیاتی مطالعہ: Reconstruction of the Judicial System in Pakistan: A Comparative and Analytical Study of the Thoughts of Syed Abūl A‘lā Maudūdī and Muhammad Asad (Al-Qamar, 2025)
This research paper critically examines the reconstruction of Pakistan’s judicial system through a comparative and analytical study of the thoughts of two eminent Islamic thinkers—Syed Abul A‘la Maududi and Muhammad Asad. Both scholars, in their respective intellectual traditions, emphasized the establishment of a judicial structure based on the principles of Shariah, social justice, and moral integrity. Maududi viewed the Western-influenced judicial framework as inherently flawed and incapable of delivering true justice, primarily due to its detachment from divine guidance and its subservience to class and political interests. Muhammad Asad, while appreciating certain procedural strengths of Western law, argued that real justice can only be achieved through an Islamic framework rooted in equity, human dignity, and accountability before God. The study explores the philosophical foundations, systemic weaknesses, and reformative propositions advanced by these thinkers, contextualizing their ideas within Pakistan’s constitutional and legal developments since 1947. The paper further highlights practical implications for the integration of Islamic legal ethics into contemporary governance structures, aiming to balance Shariah compliance with modern judicial efficiency. Ultimately, the research underscores the need for an ethically sound, socially responsive, and spiritually guided judiciary in Pakistan that reflects the vision of Maududi and Asad for a truly Islamic state.
Keywords: Islamic Justice, Maududi, Muhammad Asad, Judicial Reform, Pakistan, Shariah, Comparative Study